2019
DOI: 10.1111/ijcp.13449
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk with androgen deprivation therapy

Abstract: Summary Background From the primary care perspective, many urologists and oncologists appear to be ignoring an FDA warning to assess patients' cardiovascular (CV) risk before instituting androgen deprivation therapy (ADT) with gonadotropin‐releasing hormone (GnRH) agonists. A growing body of data suggest an association between ADT and CV/cardiometabolic risk, particularly for GnRH agonists. Methodology The author examined available evidence regarding CV side effects with GnRH agonists and antagonists to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Moreover, the correlation between OAG and ischemic stroke or coronary heart disease had been demonstrated in previous researches [17,18]. ADT can lead to a higher rate of cardiovascular disorders and related mortality [19], and a previous study showed that the incidence of OAG decreased in prostate cancer patients who received ADT therapy [20]. Accordingly, ADT may have the chance to alter the rate of OAG; however, further research is needed to confirm this.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the correlation between OAG and ischemic stroke or coronary heart disease had been demonstrated in previous researches [17,18]. ADT can lead to a higher rate of cardiovascular disorders and related mortality [19], and a previous study showed that the incidence of OAG decreased in prostate cancer patients who received ADT therapy [20]. Accordingly, ADT may have the chance to alter the rate of OAG; however, further research is needed to confirm this.…”
Section: Introductionmentioning
confidence: 90%
“…Larger-scale trials and longer follow-up with more in-depth patient demographics and risk factors will be needed to fully understand the present risk of ADT [ 32 ]. As of now, official guidelines have only come from the FDA, who in October 2010, determined that the available evidence showed a small but significant increase in risk of CV events and mandated labels on GnRH agonists to show safety information regarding its CV risks [ 38 ].…”
Section: Cardiovascular Risk Of Hormone Therapymentioning
confidence: 99%